The Effect of Injectable Medication Procedure on the Level of Pain among Early Childhood patients - A. K. Tahir, Farida; M. Azize, Pary; N. Abdul Razzaq, Aram (Kurdistan Journal of Applied Research, 2019)
Abstract Children are often exposed to painful procedures during hospitalization. Validated age appropriate scales are available to assess pain among pediatric patients. The aim of this study is to find out the effect of injectable medication procedure on the level of pain among early childhood patients. This descriptive cross -sectional study was designed to assess the physiological and behavioral characteristic of pain using CRIES pain rating scale for both medical and surgical conditions, which contains (cry, spo2, heart rate, facial expression and sleep pattern). The study has been conducted for twelve weeks duration in the pediatric wards at medical and surgical hospitals in the Sulaimani city – Kurdistan region of Iraq between 1st March to 1st Jun 2019. Fifty early childhood aged between (1 month- 3years) were participated and assessed pre injectable medication procedure and after. CRIES pain scales were applied to the children and show that there are highly significant differences between pain and the physiological, behavior characteristics between pre and after the procedure in the p-value < .00001 such as crying was developed from high pitch crying to inconsolable in post-procedure. Consumption of O2 also increased. In terms of heart rate was increased up to 20% than baseline, while, in the post-procedure, the change was more than 20% of the baseline. Facial expression was also changed to contracted face in the post procedure. Sleeping from short interval to absent sleeping was shown. Significant variation between pre and post-procedure were assessed. Further variation between medical and surgical condition for mean score of every scale of CRIES were assessed. The implications of this study will impact on health professional’s education; practice and future research are also recommending.